Clinical Guidelines for Dentistry in China During the Coronavirus Disease 2019 Pandemic - Luo, Wen; Wang, Jing; Tang, Maoxue; Peng, Jiaming; Ma, Wenmin; Wu, Yingying (Frontiers in Dental Medicine, 2021)
Preventing the spread of Coronavirus Disease 2019 (COVID-19) has become the focus of epidemiologists as the highly infectious respiratory disease spreads primarily by close, person-to-person contact via droplets or the skin. Aerosol dissemination may occur in a closed, high-aerosol environment. The aerosols generated in oral implant procedures can pollute surrounding air and device surfaces. In this paper, we summarize prevention and control measures relating to oral implantology. We focus on the relationship between COVID-19 and implantology disease prevention and control in implant treatment procedures and imaging examinations, oral health education and perspectives, and guidance for the practice of oral implantology during the COVID-19 pandemic to provide a consistent and broadly endorsed standard for dental hospital and clinics.